Elephant death, possibly by constipation - Vyas, Dhaval; Goodwin, Thomas; Rasmussen, L.; Schulte, Bruce (Pachyderm, 2005)
This article reviews the observations and analysis concerning the death of a wild juvenile male elephant which apparently died from constipation, probably from eating sisal, a plant rarely eaten by elephant. When the young animal was first seen in the vicinity of a waterhole on Ndarakwai Ranch in Tanzania on Decmber 21 2004 the researchers noted its rather odd behaviour. The juvenile was seen several times between that date and its death on Janury 3, 2005. Although at first it appeared to be part of a family unit the young male spent little time with other young elephants or specific adults. What appeared to be a protuding bolus was evident on the first day of observation. The young male spent a significant amount of time rubbing on trees and soaking in the mud, but was rarely seen drinking, eating or interacting with other its own age or younger. Examination of the carcass confirmed constipation probably caused by ingesting sisal. The faeces contained prickles and the undigested fibres of the sisal had formed long cables.